2019
DOI: 10.1109/tvlsi.2018.2884742
|View full text |Cite
|
Sign up to set email alerts
|

Black-Hat High-Level Synthesis: Myth or Reality?

Abstract: Hardware Trojans are a major concern for integrated circuits and all parts of the electronics supply chain are vulnerable to this threat. Trojans can be inserted directly by a rogue employee or through a compromised computer-aided design (CAD) tool at each step of the design cycle, including an alteration of the design files in the early stages and the fabrication process in a third-party malicious foundry. While Trojan insertion during the latter stages has been largely investigated, we focus on High-Level Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…An attacker can utilize malicious processors to violate operating system exceptions and modify the open-source processor to create a malicious firmware [71]. Prior works have also demonstrated that Trojans can be introduced during EDA design flow and high-level synthesis [72], [73]. Additionally, Trojan can be activated under unexpected conditions or by silicon wear-out [74], [75].…”
Section: Machine Learning For Hardware Securitymentioning
confidence: 99%
“…An attacker can utilize malicious processors to violate operating system exceptions and modify the open-source processor to create a malicious firmware [71]. Prior works have also demonstrated that Trojans can be introduced during EDA design flow and high-level synthesis [72], [73]. Additionally, Trojan can be activated under unexpected conditions or by silicon wear-out [74], [75].…”
Section: Machine Learning For Hardware Securitymentioning
confidence: 99%
“…Semiconductor companies commonly use third party EDA tools, third party IPs (3PIPs), and untrusted foundries. Insertion of Trojans during EDA design flow and high-level synthesis has been both demonstrated by [11], [12]. Malicious processors can be designed to allow users to violate Operating System exceptions and operate on a malicious firmware by modifying the open source processor [13].…”
Section: Background a Hardware Trojansmentioning
confidence: 99%
“…Pre‐silicon and post‐silicon Trojan detection techniques are also needed to be applied. Overhead : The cost of developing CAD tools independently is high. However, there will be security threats when using third‐party CAD tools. Case studies : Pilato et al [86] demonstrated the CAD threats by compromising a high‐level synthesis tool to insert three HTs. The payloads of these Trojans are adding latency, compromising the security of crypto‐cores, and draining energy, respectively.…”
Section: Cad Tools Attacksmentioning
confidence: 99%
“…Case studies : Pilato et al [86] demonstrated the CAD threats by compromising a high‐level synthesis tool to insert three HTs. The payloads of these Trojans are adding latency, compromising the security of crypto‐cores, and draining energy, respectively.…”
Section: Cad Tools Attacksmentioning
confidence: 99%